Virtually Regular Modules - Buyukasik, Engin; Büyükaşık, Engin; Demir, Ozlem Irmak (World Scientific Publ Co Pte Ltd, 2025)
In this paper, we call a right module M (strongly) virtually regular if every (finitely generated) cyclic submodule of M is isomorphic to a direct summand of M. M is said to be completely virtually regular if every submodule of M is virtually regular. In this paper, characterizations and some closure properties of the aforementioned modules are given. Several structure results are obtained over commutative rings. In particular, the structures of finitely presented (strongly) virtually regular modules and completely virtually regular modules are fully determined over valuation domains. Namely, for a valuation domain R with the unique nonzero maximal ideal P, we show that finitely presented (strongly) virtually regular modules are free if and only if P is not principal; and that P = Rp is principal if and only if finitely presented virtually regular modules are of the form R-n circle plus (R/Rp)(n)(1) circle plus (R/Rp(2))(n)(2) circle plus center dot center dot center dot circle plus (R/Rp(k))(n)(k) for nonnegative integers n, k, n(1), n(2),...,n(k). Similarly, we prove that P = Rp is principal if and only if finitely presented strongly virtually regular modules are of the form R-n circle plus (R/Rp)(m), where m,n are nonnegative integers. We also obtain that, R admits a nonzero finitely presented completely virtually regular module M if and only if P = Rp is principal. Moreover, for a finitely presented R-module M, we prove that: (i) if R is not a DVR, then M is completely virtually regular if and only if M congruent to( R/Rp)(m); and (ii) if R is a DVR, then M is completely virtually regular if and only if M congruent to R-n circle plus ( R/Rp)(m). Finally, we obtain a characterization of finitely generated virtually regular modules over the ring of integers.
Keywords: Regular Rings; Strongly Regular Modules; Virtually Regular Modules; Valuation Domains